Sustainable Municipal Reform in Ukraine: Theoretical Foundations and European Integration Perspectives - Kozin, Anastasiia; Kozin , Serhii; Kovach , Denis; Brulevych, Volodymyr; Kovach, Olena (European Journal of Sustainable Development, 2025)
The relevance of the study is determined by the ineffectiveness of the local self-government reform in Ukraine, in particular, the lack of autonomy of local authorities. The purpose of the article is to carry out a comprehensive analysis of the regulatory and legal framework of the activities of local self-government bodies, and the state in the area of local self-government reform. The leading methods of research have become dialectical (when defining the reform itself); general methods of synthesis and analysis (when defining the concepts of "reform", "local self-government bodies", "municipal power", etc.); comparative and legal method (when examining relevant sources, scientific texts, international legislation). It is determined that the problem of local self-government reform is a very urgent problem for Ukrainian society; it is characterized by inadequate legislation, difficult socio-economic situation, and mass ignorance of the population regarding their rights to participate in solving issues of local importance, as well as the forms of exercising such rights. The above is related to improperly conducted work of local authorities with the population. The need to take measures for the effective implementation of local self-government reform in Ukraine based on foreign experience is proven. Keywords: state reforms; local self-government reform; reform measures; the right of citizens to local self-government; local councils and executive bodies.